Peningkatan Daya Hambat Daun Manukan (Rhinacanthus Nasutus (L) Kurz) Terhadap Jamur Candida Albicans Secara In Vitro - Sunarti Narti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Fungal infections continue to increase, this is because Indonesia is a tropical country that has high temperature and humidity, and many types of fungi are resistant to antibiotic drugs. It is hoped that this situation can be prevented by administering the extract of the leaves of Manukan (Rhinacanthus nasutus (L) Kurz) which has the active ingredient Rhinacanthin. The experimental research method was to test the effectiveness of Manukan (Rhinacanthus nasutus (L) Kurz) leaf extract in inhibiting the growth of Candida albicans fungi with extract concentrations of 15, 30 and 60% respectively. Data were evaluated using the completely randomized design method by comparing static groups (static group comparison) and positive and negative controls, as many as 5 groups. The results showed that the average diameter of the inhibition zone at extract concentrations of 15, 30, and 60% were 10.95 mm, 12.10 mm, and 18.92 mm. Negative control 0.00 and positive control 23.09, so it can be concluded that the ethanol extract of Manukan leaves is effective against the inhibition of the growth of the fungus Candida albicans.